An Investigation of Insulating Paper Effect on Gas and Aging on Mineral Oil Transformer - Aulidina Dwi Nur Andriyanti; I Made Yulistya Negara; I Gusti Ngurah Satriyadi Hernanda; Daniar Fahmi (JAREE (Journal on Advanced Research in Electrical Engineering), 2022)
A transformer is an essential component in a generator, electrical equipment that works non-stop to support electricity needs. There has been a lot of thermal and electrical activity that the presence of an oil-paper insulator can suppress. The insulating ability can decrease and lead the failure due to the aging of the insulator by heating, moisture, and impurities. The aging of the paper was unavoidable, which caused the cellulose bond to break and form dissolved gases with oil, such as Carbon monoxide, Carbon dioxide, Methane, Acetylene, Ethylene, and Ethane. So, conventional dissolved gas analysis (DGA) was used to investigate further. The use of paper insulation with a certain amount affects the electrical strength of the insulator. A breakdown test on AC voltage is carried out for the following investigation. The result showed that the percentage of paper had an optimum number to get high insulator strength. By heating mineral oil for 250 hours and 500 hours, carbon monoxide and carbon dioxide are released in the different results as the DGA test. It can be concluded that cellulose paper has affected mineral oil's dissolved gas and insulator strength.